Analysis on the Grinding Quality of Palm Oil Fibers By Using A Combined Grinding Equipment - Gan, Leong Ming; Gan, Hui Leng; Law, Hoon Chit (IOP Publishing, 2015)
As known, Malaysia is the second largest palm oil producer worldwide after Indonesia, therefore indicating the abundance of its wastes within the country. The plantation would be seen to increase to at least 5.2 million ha by 2020, and the waste generation would be 50-70 times the plantation. However, the efficiency of bulk density is reduced. This is one of the main reasons of the initiation of this size reduction/ grinding research. With appropriate parameters, grinding will be seen to be helping in enhancing the inter-particle bindings, subsequently increasing the quality of final products. This paper focuses on the grinding quality involving palm oil wastes by using the Scanning Electron Microscope (SEM). The samples would first be ground to powder at varying grinding speed and finally got the randomly chosen particles measured to obtain the size range. The grinding speed was manipulated from 15 Hz to 40 Hz. From the data obtained, it was found the particles fineness increased with increasing grinding speed. In general, the size ranged from 45 μm to about 600 μm, where the finest was recorded at the speed of 40 Hz. It was also found that the binding was not so encouraging at very low speeds. Therefore, the optimum grinding speed for oil palm residues lied in the range of 25 Hz to 30 Hz. However, there were still limitations to be overcome if the accuracy of the image clarity is to be enhanced.